2003
DOI: 10.2527/2003.8192279x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of low-ash poultry meal as a protein source in canine foods1

Abstract: Eight mature female dogs (18.0 +/- 0.2 kg) were used in a replicated 4 x 4 Latin square experiment to determine the feeding value of low-ash poultry meal (PM) in a complete food fed to dogs. All foods contained graded concentrations of PM (10.4 to 32.5% DM), resulting in foods that were 10, 15, 20, and 25% CP. Daily DMI averaged 284 +/- 14 g/d. An increase in PM resulted in an increase in fecal moisture from 44.7 to 55.1% (linear; P < 0.01), and fecal DM output increased from 24.8 to 31.6 g/d (linear; P < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 10 publications
6
28
0
Order By: Relevance
“…Therefore, greater protein digestibility was observed for the HP diets, resulting in greater fecal scores and moisture. This was in agreement with the results of Yamka et al (2003), who reported the total tract apparent digestibility of PM diets in dogs fed increasing concentrations of dietary CP.…”
Section: Effect Of Protein Contentsupporting
confidence: 83%
See 2 more Smart Citations
“…Therefore, greater protein digestibility was observed for the HP diets, resulting in greater fecal scores and moisture. This was in agreement with the results of Yamka et al (2003), who reported the total tract apparent digestibility of PM diets in dogs fed increasing concentrations of dietary CP.…”
Section: Effect Of Protein Contentsupporting
confidence: 83%
“…Nevertheless, it has been shown that, even if the ratio between endogenous N loss and protein intake decreases, it remains greater with decreased protein intake in pigs and dogs (Yamka et al, 2003). Additionally, microbial metabolism in the hindgut, protein hydrolysis, and de novo synthesis will lead to major changes in fecal protein content (Yamka et al, 2003). Therefore, greater protein digestibility was observed for the HP diets, resulting in greater fecal scores and moisture.…”
Section: Effect Of Protein Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is explained by the increased large intestinal N fermentation as seen in diets with a higher aFD N . Yamka et al (2003) showed an increased large intestinal digestibility with increasing IN N in dogs fed low-ash poultry meal as a protein source. As increased large intestinal fermentation occurs with increasing IN N , sID N is lower at the same aFD N .…”
Section: Discussionmentioning
confidence: 99%
“…Although 5 other studies were found to report apparent ileal CP and AA digestibility values in adult dogs, their data were not used in the present study. Zuo et al (1996) did not report the DM content of the diets and Hill et al (2001), Yamka et al (2003Yamka et al ( , 2005, and Johnson et al (1998) investigated the digestibility of diets containing only a single protein source. A simulation model was developed, using the various relationships derived, to estimate sID of N, EAA, and NEAA for 10 diets varying in CP content and apparent aFD N for an adult dog of 20 kg BW.…”
Section: Discussionmentioning
confidence: 99%